Degradation and stabilization of lithium cobalt oxide in aqueous electrolytes. Issue 5 (20th April 2016) - Ramanujapuram, Anirudh; Gordon, Daniel; Magasinski, Alexandre; Ward, Brian; Nitta, Naoki; Huang, Cindy; Yushin, Gleb
Abstract : We report herein the exceptional cycle stability of lithium cobalt oxide (LCO) in aqueous electrolytes of high lithium salt concentrations. Abstract : We report herein the exceptional cycle stability of lithium cobalt oxide (LCO) in aqueous electrolytes of high lithium salt concentrations. We demonstrate retention of up to 87% of the initial discharge capacity after 1500 cycles at a 1C charge–discharge rate. We also demonstrate that LCO, when in contact with each of the aqueous electrolytes tested, exhibits a high electrode potential and a large initial discharge capacity, similar to that of LCO electrochemically cycled in conventional organic electrolytes. More importantly, our systematic studies and post-mortem analyses of LCO cells reveal that the primary mechanism of LCO degradation in aqueous electrolytes is the formation of a resistive layer of cobalt(ii ) oxide on the particles' surfaces. We show that higher electrolyte molarity and certain salt compositions may significantly reduce the layer thickness and dramatically improve LCO stability. These findings constitute a substantial step towards development of gravimetrically and volumetrically energy dense aqueous lithium ion batteries.